REKONSTRUKSI TRADISI RARANGKÉN PARÉ: UPAYA AWAL KONSERVASI BUDAYA PANGAN DI CIPATUJAH KABUPATEN TASIKMALAYA - Gumilar, Trisna; CMS, Samson; Kusnandar, Kusnandar (Indonesian Journal of Conservation, 2016)
Reconstruction Rarangkén Paré is early conservation efforts undertaken in the food culture village Kecamatan Cipatujah Sindangkerta Tasikmalaya regency. Rarangkén Paré is a series of activities ranging from maintaining rice selecting and preparing a superior seeds, preserve, maintain, harvest, store, process until the rice into the rice, and cook it into food. Reconstruction is done with the stages of implementation procedures are structured based on a realistic and holistic involving researchers, partners, and society as well as support from the local village government. There are two main dimensions, namely cultural reconstruction Rarangkén Paré retrospective reading and reading perspective. Readings retrospective, ie digging up information in a way look 'backward' tradition rarangken paddy to find symbolic meanings. Prospective readings Rarangkén Paré is a new interpretation, that is, finding opportunities creativity and productivity. Rekonstruksi Rarangkén Paré adalah upaya awal konservasi budaya pangan yang dilakukan di desa Sindangkerta KecamatanCipatujah Kabupaten Tasikmalaya. Rarangkén Paré adalah rangkaian kegiatan memelihara padi mulai dari memilih dan menyiapkan benih yang unggul, memelihara, menjaga, memanen, menyimpan, mengolah padi hingga menjadi beras, dan memasaknya menjadi makanan. Rekonstruksi dilakukan dengan tahapan-tahapan terstruktur berdasarkan prosedur pelaksanaan yang realistik dan holistik yang melibatkan peneliti, mitra, dan masyarakat serta dukungan dari pemerintah desa setempat. Terdapat dua dimensi utama rekonstruksi budaya Rarangkén Paré yaitu pembacaan restropektif dan pembacaan perspektif . Pembacaan restropektif, yaitu menggali informasi dengan cara menengok ‘ke belakang’ tradisi rarangken sawah untuk menemukan makna-makna simbolik. pembacaan prospektif adalah tafsir baru Rarangkén Paré, yaitu menemukan berbagai peluang kreativitas dan produktivitas.